Stable Electrochemical Measurements of Platinum Screen-Printed Electrodes Modified with Vertical ZnO Nanorods for Bacterial Detection. (1st August 2019) - Nguyen, Thi Hong Phuoc; Tonezzer, Matteo; Dang, Thi Thanh Le; Vu, Quang Khue; Tran, Quang Huy; Nguyen, Duc Hoa; Nguyen, Van Hieu
Abstract : The study is aimed at investigating the stability of electrochemical and biosensing properties of ZnO nanorod-based platinum screen-printed electrodes (SPEs) applied for detection of bacterial pathogens. The platinum SPEs were designed and patterned according to standard photolithography and lift-off process on a silicon wafer. ZnO nanorods (NRs) were grown on the platinum working electrode by the hydrothermal method, whereas Salmonella polyclonal antibodies were selected and immobilized onto ZnO NR surface via a crosslinking process. Morphological and structural characteristics of ZnO NRs were investigated by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD). The results showed that the ZnO NRs were grown vertically on platinum electrodes with a diameter around 20-200 nm and a length of 5-7  μ m. These modified electrodes were applied for detection of Salmonella enteritidis at a concentration of 10 3  cfu/mL by electrochemical measurements including cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The ZnO NR-modified platinum electrodes could detect Salmonella bacteria well with stable measurements, and the signal to noise ratio was much higher than that of 3 : 1. This study indicated that ZnO NR-modified platinum SPEs could be potential for the development of biochips for electrochemical detection of bacterial pathogens.